GENERATING OF OPTIMAL QUANTIZATION LEVELS OF CONTROL CURRENTS FOR LINEAR STEPPING DRIVES OF PRECISION MOTION SYSTEMS - I. V. Dainiak; V. P. Oger; D. S. Tsitko; D. G. Begun (Наука и техника)
The paper proposes a method of taking into account accumulated and temperature errors while forming coordinate discrete grid of a linear stepping drive. An algorithm for determination of optimal quantization levels of control currents of drive's phases has been developed in the paper; it minimizes an error of positioning that forms correction files for application of a control system in the software. Investigations on stability of discrete grid nodes coordinates have been carried our with the help of a monitoring station for accurate parameters of linear stepping drive. The investigations have proved an efficiency of the proposed algorithm and methodology for forming coordinate discrete grid.